2014
DOI: 10.5210/ojphi.v5i3.4996
|View full text |Cite
|
Sign up to set email alerts
|

Android and ODK based data collection framework to aid in epidemiological analysis

Abstract: Periodic collection of field data, analysis and interpretation of data are key to a good healthcare service. This data is used by the subsequent decision makers to recognize preventive measures, provide timely support to the affected and to help measure the effects of their interventions. While the resources required for good disease surveillance and proactive healthcare are available more readily in developed countries, the lack of these in developing countries may compromise the quality of service provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
See 1 more Smart Citation
“…-To propose new tools compatible with the ODK suite or with the ODK-X suite [20], [21], [22], [23], [24]; -To make improvements to a single component of the ODK suite or the ODK-X suite, without having to touch all the others [25], [26]; -To use one or some of the components of the ODK or ODK-X suite without having to use the whole suite. The tools of the two suites can even be used with other technologies that do not belong to ODK [31], [32], [34], [38], [40], [41]; -To extend a component of the ODK or ODK-X suite by adding new functionalities and then to use this extension with the other components of the suite [27], [28], [29].…”
Section: Table-iii: Studied Articles By Themementioning
confidence: 99%
“…3 [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [15], [40], [41], [42], [43] Use case of ODK. 15…”
Section: Referencesmentioning
confidence: 99%
“…This includes tasks posed over Amazon's Mechanical Turk, as an example (Buhrmester et al, 2011;Kittur et al, 2008), as well as reaching more far-flung rural populations directly via smartphones equipped with Android ODK (Brunette et al, 2013). While many of the latter applications have focused on collecting clinical data (Raja et al, 2014;Rajput et al, 2012), applications are in development that gather a broader range of socio-economic and experimental data (e.g., Enenkel et al, 2015).…”
Section: Data Collection Under Ictsmentioning
confidence: 98%
“…Some researchers (e.g., Enenkel et al, 2015;Raja et al, 2014) have invested in custom user interfaces to launch individual survey tasks within ODK. Custom interfaces allow for visual cues, notifications, scheduling of tasks, among other capabilities of Android-enabled devices.…”
Section: Best Next Stepsmentioning
confidence: 99%
“…Growing evidence has demonstrated that mobile health (mHealth) platforms make it possible for healthcare professionals to monitor patient conditions constantly and remotely on the one hand, and on the other hand these mHealth platforms can empower patients to manage their own diseases [2][3][4][5][6][7][8][9][10][11][12]. In other words, mobile technologies may optimize healthcare practices by enabling professionals to conveniently collect and utilize large amounts of patient data in their clinical practice [13,14]. In this model, convenient data collection, integration, and reporting is of critical importance.…”
Section: Introductionmentioning
confidence: 99%